Customer satisfaction towards services provided by Time Systems Integrators Sdn. Bhd. for PPSMI phase two in Pudu Zone, Kuala Lumpur - Muhd Mustafa, Ahmad Faisal (2005)
The purpose of this research is to study the customer satisfaction towards the services provided by TIME Systems Integrators in Pudu Zone, Kuala Lumpur and the relationship between service quality, after sales service and corporate image with customer satisfaction. Moreover, this study will examine and measure the level of customer satisfaction and the relationships of all the items that will influence their satisfaction with the services provided to them. The findings showed that most of the customers were satisfied with the services provided by TIME System Integrators to them. Service quality, after sales service and corporate image have a strong relationship with customer satisfaction and the correlation of coefficient is also high. The researcher is also able to give some recommendations and suggestions on how to improve and increase customer satisfaction after the analysis, findings and interpretation were made. In this study, we used interviews and questionnaire and other secondary sources such as reports, database and so on for data collection. Based on frequency, cross tabulation and ANOVA test, a clear findings and results are observed